Termini in der technischen Übersetzung: Rettungsanker, Tyrannen – oder auch nur Wörter? - Oster, Ulrike (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The understanding of ‘term’ in traditional terminology theory reduces the lexical problems of technical translation to a mere substitution of the source-text term by a target-text term. In translation studies however , a number of issues have been highlighted which are not covered by traditional terminology theory, e.g. cultural specificity or the importance of textual and pragmatic considerations. This paper first analyses how the new communication and cognition-oriented approaches to terminology account for these aspects of technical translation. Then it briefly presents results of a language-pair and domain-specific study which allows us to exemplify some of the issues that have been discussed and to reach some specific conclusions for the translator of this linguistic combination.